Get ready to innovate! Staff`s disposition to implement service innovation in non-profit sport organisations - Winand, M.; Anagnostopoulos, C. (International Journal of Sport Policy and Politics, 2017)
While sport entrepreneurs are known for being risk-takers and for being proactive when implementing new ideas, little is known about individuals` attitudes within non-profit sport organisations (NPSO). The present study draws on policy implementation and innovation theories to address this gap by investigating staff attitudes towards newness and its impact on innovativeness and change. An online survey was administered to representatives of regional sport federations in Belgium (n = 101; 70% response rate) in order to measure their attitude towards newness, the number of service innovation successfully implemented and the levels of innovativeness and organisational change perceived. On average, sport federation staffs show a positive attitude towards newness, which supports the implementation of service innovation. The number of service innovations and perceptions of innovativeness both have significant indirect effects on organisational change as perceived by individuals within sport federations. Managerial and policy implications are provided with regard to the need to develop positive attitude towards newness within NPSOs in order to foster innovation.